EFEKTIVITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DENGAN ANJUNGAN DUKCAPIL MANDIRI (ADM) PADA DINAS KEPENDUDUKANDAN PENCATATAN SIPIL KABUPATEN TABALONG - Siti Paulina; Norhatipah. H (SINERGI : Jurnal Riset Ilmiah, 2026)
Population administration services are an important part of public services that demand effectiveness and quality of service. In line with the development of information technology, the Population and Civil Registration Department of Tabalong Regency has implemented an innovative service called the Independent Civil Registration Counter (ADM). However, its implementation still faces obstacles such as a lack of public awareness and limited assistance from officers during peak hours. This study aims to analyze the effectiveness of population administration services through ADM. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews, and documentation. The results show that population administration services through ADM are quite effective, reviewed from the variable of adaptability, communication indicators are less effective because there is still no socialization, especially and many people are still unfamiliar with services using ADM, the cooperation indicator is effective. The variables of work performance, skills, discipline, and personality indicators are effective, while the cooperation indicator is considered quite effective. Finally, the variables of job satisfaction, job content indicators, supervision, organization and management, opportunities for advancement, and salary and finance are considered effective.  The influencing factors include: inhibiting factors, minimal outreach, and suboptimal service delivery by officers during peak hours. To improve the satisfaction and quality of public services, it is recommended that the Population and Civil Registration Service of Tabalong Regency should improve the communication aspects related to the existence of ADM in various media, both online and offline, and the public should be proactive in utilizing services with ADM in order to improve the quality of communication and effective services